Students satisfaction in foods by cafeteria of UiTM Dungun / Azira Amran, Nurul Akhmar Asmidar Makhtar & Syed Ahmad Asyraf Syed Hazani - Amran, Azira; Makhtar, Nurul Akhmar Asmidar; Syed Hazani, Syed Ahmad Asyraf (2012)
This study is to find “ The students satisfaction in food by cafetaria of UiTM Dungun. The population for this study is among degree level of students. We have distributed 280 sample but the total of the sample that researchers got back were 250 only. This study adopts a questionnaire as the instrument. The students satisfaction that we looked is regarding the price of foods, quality, quantity, tastes of food also the varieties. In order to find out this relationship, the convenience sampling been choose. To evaluate this study the criteria such as service approaches, customer needs and want, new opportunity and result are the term that can contribute this study. The results of this study can be used by the cafetaria to enhance level of satisfaction of students regarding the food served.